How to protect agricultural workers from exposure to pesticides: Effectiveness of woven and natural resin-coated fabrics. Issue 1 (1st January 2021) - Sapbamrer, Ratana; Naksata, Manoch; Hongsibsong, Surat; Wunnapuk, Klintean; Watcharapasorn, Anucha; Chittrakul, Jiraporn
Abstract: Agricultural workers in low and middle-income countries usually wear their everyday clothing made of woven fabrics during pesticide application. Different characteristics of various woven fabrics have different abilities to prevent the penetration of pesticides through to the skin. Therefore, the ultimate goal of this study is that agricultural workers in Thailand can choose a suitable fabric of protective clothing to protect themselves from pesticide exposure. This study aims to investigate pesticide penetration levels in different woven fabrics, and to explore factors affecting levels of pesticide penetration through fabrics. In addition, our study aims to produce cotton fabrics coated with a natural resin to obtain water-repellent characteristics and evaluate their effectiveness in protecting against pesticides. Four pesticides used in the testing process were chlorpyrifos, cypermethrin, paraquat, and glyphosate. The results found that a suitable fabric to protect agricultural workers from pesticide exposure is a fabric which made of 100% cotton and have greater weight. With regard to natural resin-coated fabrics, fabric C1-R showed the highest levels of effectiveness in protecting against the pesticides (range between 89%-95%). The natural resin-coated fabric is an alternative fabric in the protection against pesticides for agricultural workers in low and middle-income countries when commercial PPE are prohibitively expensive.